Women of color in STEM : navigating the double bind in higher education - Irby, Beverly J.; Abdelrahman, Nahed; Polnick, Barbara; Ballenger, Julia, 1949- (Research on women and education., 2021)
"Though there has been a rapid increase of women's representation in law and business, their representation in STEM fields has not been matched. Researchers have revealed that there are several environmental and social barriers including stereotypes, gender bias, and the climate of science and engineering departments in colleges and universities that continue to block women's progress in STEM. In this book, the authors address the issues that encounter women of color in STEM in higher education"--